A high performance chromium bronze rod and preparation method thereof

By controlling the structure of the Cr precipitation phase and introducing specific elements, combined with advanced technology methods, high-performance chromium bronze rods are prepared, which solves the problem of softening of existing materials at high temperatures and achieves higher conductivity and tensile strength and softening temperature to meet the stable working needs of high-temperature switches.

CN116479283BActive Publication Date: 2025-02-18JINTIAN COPPER GROUP CORP NINGBO
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202310310626.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-28
Publication Date
2025-02-18
Estimated Expiration
2043-03-28

AI Technical Summary

Technical Problem

The existing chromium bronze material softens under high temperature conditions, resulting in the failure of the high-temperature switch, posing safety hazards, and cannot meet higher equipment requirements.

Method used

By controlling the size, morphology and crystal structure of the Cr precipitation phase, Ti, Ag, and Mg elements were introduced, and high-performance chromium bronze rods were prepared by using semi-continuous casting, electromagnetic stirring, water sealing and aging technology.

Benefits of technology

It significantly improves the conductivity, tensile strength, softening temperature and high temperature stability of the material, and can meet the needs of materials for high-temperature switching in the future, so that it can work stably under high temperature conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116479283B_ABST
    Figure CN116479283B_ABST
Patent Text Reader

Abstract

A high-performance chromium bronze rod and a preparation method thereof, wherein the alloy composition of the chromium bronze rod is Cr: 0.2-0.65%, Ti: 0.1-0.5%, Ag: 0.1-0.5%, Mg: 0.1-0.5%, Cu balance, and the percentage of each element above is mass percentage. The preparation process is: semi-continuous casting + electromagnetic stirring → water seal extrusion → pickling → drawing → finished product aging. The alloy element ratio of the present invention is scientific and reasonable. By introducing Ti, Ag, and Mg alloy elements, the size, morphology, and crystal structure of the Cr precipitation phase are controlled, and the strength, electrical conductivity, softening temperature and other properties of the material are improved. The preparation process is simple. The prepared chromium bronze rod has an electrical conductivity of ≥85% IACS, a tensile strength of ≥650Mpa, a softening temperature of ≥650℃, A100mm ≥20%, and a hardness of ≥90HRB, which can meet the requirements of future high-temperature switch materials and enable it to work stably under high temperature conditions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a chromium bronze material and a preparation method thereof, in particular to a high-performance chromium bronze rod and a preparation method thereof. Background Art

[0002] A high temperature switch is a switch that can work stably for a long time in a high temperature environment. It is mainly used in large equipment in metallurgy, machinery, mining, electric power, chemical industry and other industries, and is an important part of large equipment. The quality of the high temperature switch determines the stability of the equipment operation. When large equipment is running, it requires hundreds or even thousands of amperes of current to drive it. This requires the materials used to make high temperature switches to have high conductivity and the ability to withstand high temperatures for a long time. At present, the material used to make high temperature switches is chromium bronze. Chromium bronze rods have high strength and hardness at room temperature and below 400°C, good electrical conductivity and thermal conductivity, and good processing and forming performance. However, with the rapid development of industries such as metallurgy, machinery, and mining, the requirements for equipment are getting higher and higher. Ordinary chromium bronze materials such as C18200 can no longer meet higher requirements. The main reason is that their softening temperature is low. When high temperature softening occurs, the high temperature switch is easily ineffective, causing safety hazards.

[0003] After investigation, the existing Chinese patent No. 200810049742.8, "A chromium bronze alloy plate for crystallizer and its processing technology", is composed of copper: balance, chromium: 0.4-1.5%, and total impurities: ≤0.2%. The processing technology is: melting, milling, sawing, heating, hot rolling, leveling, pickling, flaw detection, shearing, warehousing, etc. This material is used for crystallizers and cannot meet the needs of high-temperature switch materials.

[0004] Therefore, it is necessary to develop a new chromium bronze material to meet the requirements of future high-temperature switches so that it can work stably under high temperature conditions. Summary of the invention

[0005] The first technical problem to be solved by the present invention is to provide a high-performance chromium bronze rod with high electrical conductivity and high temperature resistance.

[0006] The second technical problem to be solved by the present invention is to provide a method for preparing high-performance chromium bronze rods, by controlling the size, morphology and crystal structure of the Cr precipitated phase, thereby improving the strength, electrical conductivity, softening temperature and other properties of the material.

[0007] The technical solution adopted by the present invention to solve the above-mentioned first technical problem is: a high-performance chromium bronze rod, characterized in that the alloy composition of the chromium bronze rod is Cr: 0.2-0.65%, Ti: 0.1-0.5%, Ag: 0.1-0.5%, Mg: 0.1-0.5%, and Cu as the balance, and the percentages of the above elements are mass percentages.

[0008] When the eutectic temperature is 1072°C, the maximum solubility of Cr in Cu is 0.65%. It is strengthened by quenching-cold deformation-aging treatment. When Cr atoms are dissolved in Cu, a supersaturated solid solution is formed, which will produce solid solution strengthening. The reason is that lattice distortion is generated, which causes the internal energy of the material to increase, the micro stress increases, and the dislocation slip deformation is hindered. However, the scattering rate of electrons increases, so that the strength, hardness, and softening temperature of the material are improved, and the conductivity is sharply reduced. When aging is carried out, the supersaturated solid solution decomposes, and the alloy elements are precipitated in a certain way and dispersed in the matrix to form a precipitation phase. The precipitation phase can effectively prevent the movement of grain boundaries and dislocations, thereby improving the hardness, tensile strength, conductivity, softening temperature and other properties of the material. The Cr content of the present invention is 0.2-0.65%. When the Cr content is lower than 0.2%, the solid solution strengthening effect is weak, and the performance improvement of the material after aging precipitation is small. When the Cr content is higher than 0.65%, it will not produce the solid solution aging strengthening effect, but will be dispersed in the matrix in the form of particles. Although it can also improve the strength, softening temperature and other properties of the material, it will reduce the conductivity of the material. Particularly preferred is: 8nm≤Cr precipitate phase size≤15nm, the shape is approximately spherical, 1≤aspect ratio≤1.2, and the number of fcc face-centered cubic lattices is ≥98%. When the Cr precipitate phase size is less than 8nm, the material is in an under-aged state, the Cr phase dissolved in the copper matrix has not been completely precipitated, the lattice distortion generated in the matrix is ​​large, the scattering effect on electrons is increased, and the conductivity of the material is reduced. When the Cr precipitate phase size is greater than 15nm, the material is already in an over-aged state, its slip resistance to dislocations is reduced, the strength of the material is reduced, and the scattering effect on electrons is increased, reducing the conductivity of the material. The way in which dislocations pass through the precipitate phase is mainly the cutting mechanism, so when the precipitate phase shape is approximately spherical, the greater the resistance to dislocation cutting, the greater the strength of the material can be improved.

[0009] The introduction of Ti element promotes the precipitation of Cr phase, refines the grains, forms Ti2Cu and TiCu phases to produce aging strengthening, and improves the strength, conductivity and softening temperature of the material. (1) The diffusion rate of Ti atoms in the copper matrix is ​​much greater than that of Cr atoms, which inhibits the crystal structure transformation of Cr particles from fcc to bcc, enhances the ability of Cr particles to hinder dislocation slip, and improves the strength of the material. (2) The Cr precipitated phase will not grow rapidly during the aging process. At the same time, the added Ti element promotes the precipitation of Cr phase, which increases the conductivity of the alloy. (3) The addition of Ti increases the critical supercooling of the liquid-solid phase transition, reduces the critical nucleation radius of the alloy, increases the nucleation rate, refines the grains, and improves the strength of the alloy. (4) The formation of aging strengthening phases Ti2Cu and TiCu hinders dislocation movement, increases dislocation density, and thus improves the strength of the material. The Ti element content of the present invention is 0.1-0.5%. If the content is higher than 0.5%, more Ti2Cu and TiCu phases are generated. After aging, most of them are precipitated to the grain boundary, and the scattering effect on electrons increases, resulting in a decrease in the conductivity of the product. If the content is lower than 0.1%, Cr will not be completely precipitated, and a part of it is still dissolved in the matrix, resulting in lattice distortion, improving the strength, softening temperature and other properties of the material, but its scattering effect on electrons is large, which seriously reduces the conductivity of the material. It is particularly preferred that: 10nm≤Ti2Cu and TiCu precipitation phase size≤20nm, 1≤the aspect ratio of the two phases≤1.2, and the shape is approximately spherical. When the size of Ti2Cu and TiCu precipitation phases is less than 10nm, the material is in an under-aging state, the Cr phase dissolved in the copper matrix has not been completely precipitated, the lattice distortion generated in the matrix is ​​large, the scattering effect on electrons increases, and the conductivity of the material is reduced. When the size of Ti2Cu and TiCu precipitates is greater than 20nm, the material is already in an over-aged state, the strengthening of the material metal lattice is weakened, the slip resistance of dislocations is reduced, the strength of the material is reduced, the scattering effect on electrons is increased, and the conductivity of the material is reduced. The main way for dislocations to pass through the precipitate is the cutting mechanism, so when the shape of the precipitate is approximately spherical, the greater the resistance to dislocation cutting, the greater the strength of the material.

[0010] The introduction of Ag element has a strong solid solution strengthening effect, can reduce the distance between dendrites, inhibit the growth and diffusion of Cr precipitation phase, improve the strength and softening temperature of the material, and has little effect on the conductivity. The added Ag element is solid-dissolved in the matrix and evenly distributed, resulting in lattice distortion, which can effectively hinder the movement of dislocations, and also has a strong solid solution strengthening effect. The Ag atoms in the matrix hinder the diffusion of Cr atoms, and to a certain extent inhibit the nucleation and growth of the Cr precipitation phase. After adding the Ag element, part of the precipitation phase in the matrix is ​​distributed in an approximately spherical shape, and the fine Cr precipitation phase enables the Cu-Cr alloy to still have good softening resistance at high temperatures. The Ag content of the present invention is 0.1-0.5%. When the silver content is less than 0.1%, the nucleation and growth of the Cr precipitation phase are weakly inhibited, which reduces the performance of the material. When the silver content is higher than 0.5%, its strengthening effect is weakened, the material performance increases slowly, and it has no practical significance. Particularly preferred is: 10nm≤Ag precipitated phase size≤25nm, 1≤aspect ratio≤1.3, and shape is approximately spherical. After precipitation, Ag exists in the form of fine particles on the matrix, producing second phase strengthening. When the Ag precipitated phase size is less than 10nm, the Cr phase has not yet completely precipitated from the matrix, the strength of the material is relatively small, and the electrical conductivity is also relatively low. When the Ag precipitated phase size is greater than 25nm, the Cr phase has completely precipitated from the matrix and has grown up. In addition, the second phase strengthening effect of Ag is weakened, the slip barrier to dislocation is weakened, the strength and hardness of the material increase less, and the electrical conductivity decreases.

[0011] The introduction of Mg element accelerates the nucleation of the precipitate phase in the initial stage of alloy aging, and improves the strength, conductivity and softening temperature of the material. The addition of Mg element can accelerate the nucleation of the precipitate phase in the initial stage of alloy aging, and form a Mg-rich atom region similar to Cottrell gas around the dislocation, which has an inhibitory effect on the movement of the dislocation. In addition, since the Mg element neither reacts with Cr nor dissolves in Cr and the solubility of Mg in Cu is higher than that in Cr, during the aging process, Mg atoms will quickly diffuse out of the metastable Cr precipitate phase and concentrate at the interface between the precipitate phase and the matrix, reducing the elastic mismatch energy of the interface, eliminating the distortion energy, thereby reducing the driving force for the growth of Cr particles, and inhibiting the recrystallization process, so that the high temperature performance of the alloy is improved. In addition, the Mg element itself also has a strong solid solution strengthening effect on the alloy, and the conductivity is also slightly improved. The Mg content of the present invention is: 0.1-0.5%. When the magnesium content is less than 0.1%, the driving force for the growth of Cr particles is less affected, and the growth of Cr particles cannot be effectively inhibited. When the magnesium content is higher than 0.5%, due to the appearance of the second group, the processing performance of the material is greatly reduced, and the conductivity of the material is reduced. It is particularly preferred that: 10nm≤Mg precipitate phase size≤25nm, 1≤aspect ratio≤1.2, and it is distributed in the grain boundary in an ellipsoidal shape. After Mg precipitates, it exists on the matrix in the form of fine particles, producing second phase strengthening. When the Mg precipitate phase size is less than 10nm, the Cr phase has not yet completely precipitated from the matrix, the strength of the material is relatively low, and the conductivity is also low. When the Mg precipitate phase size is greater than 25nm, the Cr phase has completely precipitated from the matrix and has grown. In addition, the second phase strengthening effect of Mg is weakened, the slip barrier to dislocations is weakened, the strength and hardness of the material increase less, and the conductivity decreases.

[0012] Under the combined effect of Cr, Ti2Cu, TiCu, Ag and Mg precipitation phases, the microscopic dislocation density is 1.0-10.0×10 14 / mm 2 , the grain size is 5-10um.

[0013] The technical solution adopted by the present invention to solve the above second technical problem is: a method for preparing the above high-performance chromium bronze rod, characterized by comprising the following steps:

[0014] 1) Melting: The materials are prepared according to the alloy composition of the chromium bronze rod and melted in a semi-continuous casting furnace;

[0015] 2) Electromagnetic stirring: The molten copper enters the crystallizer after smelting. The superheat of the molten copper in the crystallizer is eliminated by electromagnetic stirring, and the grains of the ingot are refined to obtain an equiaxed crystal structure.

[0016] 3) Water-seal extrusion: Place the ingot into a large-tonnage reverse extruder for water-seal extrusion, with an extrusion temperature of 900-950°C, an extrusion ratio of 6-310, an extrusion speed of 3-20mm / s, and a cooling water cooling speed of 80-120°C / s;

[0017] 4) Pickling: put the extruded blank into the pickling tank for pickling;

[0018] 5) Drawing: Use a combined drawing machine to produce straight bars;

[0019] 6) Finished product aging: Under protective gas, the finished product is bright annealed at an aging temperature of 400-500℃ for 3-5h.

[0020] The water seal extrusion temperature is 900-950℃, the extrusion ratio is 6-310, the extrusion speed is 3-20mm / s, and the cooling water cooling speed is 80-120℃ / s. If the extrusion temperature is higher than 950℃, the grains will grow abnormally after extrusion, reducing the tensile strength, elongation and other properties of the material. If the extrusion temperature is lower than 900℃, after water seal extrusion, the Cr element dissolved in the copper matrix is ​​insufficient, resulting in a weakened subsequent aging strengthening effect, a reduced dislocation density, and a reduction in the conductivity, tensile strength and softening temperature of the material.

[0021] Finished product aging: Under protective gas, the finished product is bright annealed at an aging temperature of 400-500℃ for 3-5h. The protective gas is argon and the argon flow rate is 15-20m 3 / h. If the aging temperature is lower than 400℃ and the time is less than 5h, the Cr element dissolved in the copper matrix cannot be completely precipitated, the aging strengthening effect is weakened, and the conductivity, strength, elongation and softening temperature of the material are reduced. The material is in an under-aged state. If the aging temperature is higher than 500℃ and the time is more than 5h, the Cr dissolved in the copper matrix will be completely precipitated, the Cr precipitation phase and grains will grow, the strength, elongation and softening temperature of the material will be greatly reduced, and the material is in an over-aged state.

[0022] Furthermore, the raw materials prepared in step 1) according to the alloy composition of the chrome bronze rod are: cathode copper with a purity of ≥99.99%, Cu-Cr master alloy, Cu-Ti master alloy, Cu-Mg master alloy and single substance Ag with a purity of ≥99.99%. Preferably, the Ti content in the Cu-Ti master alloy is 50%, the Cr content in the Cu-Cr master alloy is 50%, and the Mg content in the Cu-Mg master alloy is 50%.

[0023] Furthermore, the process parameters of the smelting in step 1) are: casting temperature 1250-1300°C, pulling speed 55-65mm / min, cooling water temperature 20-25°C, cooling water flow rate 14-17m 3 / h.

[0024] Further, the current frequency of the electromagnetic stirring in step 2) is 10-15H Z , the current intensity is 350-400A, the number of equiaxed grains is ≥90%, and the equiaxed grain size is ≥0.01mm.

[0025] Furthermore, the pickling in step 4) refers to immersing the finished product in pickling water with a mass ratio of H2SO4:HNO3:H2O=5.7±0.1:1±0.1:12.5±0.1, and the immersion time is 20-60 minutes.

[0026] Finally, the protective gas in step 6) is argon, and the argon flow rate is 15-25m 3 / h.

[0027] Compared with the prior art, the advantages of the present invention are: the introduction of Ti, Ag, Mg alloy elements, by controlling the size, morphology, crystal structure of the Cr precipitation phase, further improves the strength, conductivity, softening temperature and other properties of the material; adopts semi-continuous casting, electromagnetic stirring, water seal extrusion and finished product aging process to improve the material's resistance to high temperature softening, tensile strength and conductivity. The present invention has a scientific and reasonable ratio and a simple preparation process. The prepared chromium bronze rod has a conductivity of ≥85% IACS, a tensile strength of ≥650Mpa, a softening temperature of ≥650℃, A100mm ≥20%, and a hardness of ≥90HRB, which can meet the requirements of future high-temperature switch materials and enable them to work stably under high temperature conditions. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 This is a metallographic structure photograph of Example 1 of the present invention (magnified 100 times). DETAILED DESCRIPTION

[0029] The present invention is further described in detail below in conjunction with embodiments and drawings.

[0030] A high-performance chromium bronze rod, characterized in that the alloy composition of the chromium bronze rod is 0.2-0.65% Cr, 0.1-0.5% Ti, 0.1-0.5% Ag, 0.1-0.5% Mg, and the remainder Cu, wherein the percentages of the above elements are mass percentages.

[0031] The raw materials used in the following embodiments are: cathode copper with a purity of ≥99.99%, Cu-Cr master alloy (Cr content 50%), Cu-Ti master alloy (Ti content 50%), Cu-Mg master alloy (Mg content 50%) and single substance Ag with a purity of ≥99.99%.

[0032] Example 1

[0033] A method for preparing a high-performance chromium bronze rod, comprising the following specific steps:

[0034] 1. Smelting: Cathode copper purity ≥ 99.99%, Cu-Cr master alloy (Cr50%), Cu-Ti master alloy (Ti content 50%), Cu-Mg master alloy (Mg content 50%), single Ag purity ≥ 99.99%, all elements are added according to mass percentage. The ingredients are shown in Table 1, and the smelting parameters are shown in Table 2.

[0035] 2. Electromagnetic stirring: The molten copper enters the crystallizer after smelting. The superheat of the copper in the crystallizer is eliminated by electromagnetic stirring, and the grains of the ingot are refined to obtain an equiaxed crystal structure.

[0036] 3. Water seal extrusion: 3150t extruder is used for water seal extrusion, the extrusion temperature is 900℃, the extrusion speed is 10mm / s, the extrusion ratio is 268, the extrusion specification is Φ16mm, and the cooling water cooling speed is 100℃ / s.

[0037] 4. Pickling: Place the Φ16mm extruded billet into a pickling tank with H2SO4:HNO3:H2O=5.7:1:12.5 (volume ratio) for pickling and soaking for 20 minutes.

[0038] 5. Drawing: Use 8t combined drawing machine for Φ14mm drawing.

[0039] 6. Finished product aging: Argon is used as the protective gas to brightly anneal the Φ14mm drawn product at 450℃ for 4h, with an argon flow rate of 25m 3 / h.

[0040] 7. Performance test: 10 samples were randomly selected for performance test. The performance is shown in Table 3.

[0041] Example 2

[0042] A method for preparing a high-performance chromium bronze rod, comprising the following specific steps:

[0043] 1. Smelting: Cathode copper purity ≥ 99.99%, Cu-Cr master alloy (Cr50%), Cu-Ti master alloy (Ti content 50%), Cu-Mg master alloy (Mg content 50%), single Ag purity ≥ 99.99%, all elements are added according to mass percentage. The ingredients are shown in Table 1, and the smelting parameters are shown in Table 2.

[0044] 2. Electromagnetic stirring: The molten copper enters the crystallizer after smelting. The superheat of the copper in the crystallizer is eliminated by electromagnetic stirring, and the grains of the ingot are refined to obtain an equiaxed crystal structure.

[0045] 3. Water seal extrusion: 3150t extruder is used for water seal extrusion, the extrusion temperature is 920℃, the extrusion speed is 7mm / s, the extrusion ratio is 268, the extrusion specification is Φ16mm, and the cooling water cooling speed is 110℃ / s.

[0046] 4. Pickling: Place the Φ16mm extruded billet into a pickling tank with H2SO4:HNO3:H2O=5.7:1:12.5 (volume ratio) for pickling and soaking for 20 minutes.

[0047] 5. Drawing: Use 8t combined drawing machine for Φ14mm drawing.

[0048] 6. Finished product aging: Argon is used as the protective gas to brightly anneal the Φ14mm drawn product at 480℃ for 4h, with an argon flow rate of 25m 3 / h.

[0049] 7. Performance test: 10 samples were randomly selected for performance test. The performance is shown in Table 3.

[0050] Example 3

[0051] A method for preparing a high-performance chromium bronze rod, comprising the following specific steps:

[0052] 1. Smelting: Cathode copper purity ≥ 99.99%, Cu-Cr master alloy (Cr50%), Cu-Ti master alloy (Ti content 50%), Cu-Mg master alloy (Mg content 50%), single Ag purity ≥ 99.99%, all elements are added according to mass percentage. The ingredients are shown in Table 1, and the smelting parameters are shown in Table 2.

[0053] 2. Electromagnetic stirring: The molten copper enters the crystallizer after smelting. The superheat of the copper in the crystallizer is eliminated by electromagnetic stirring, and the grains of the ingot are refined to obtain an equiaxed crystal structure.

[0054] 3. Water seal extrusion: 3150t extruder is used for water seal extrusion, the extrusion temperature is 950℃, the extrusion speed is 9mm / s, the extrusion ratio is 268, the extrusion specification is Φ16mm, and the cooling water cooling speed is 120℃ / s.

[0055] 4. Pickling: Place the Φ16mm extruded billet into a pickling tank with H2SO4:HNO3:H2O=5.7:1:12.5 (volume ratio) for pickling and soaking for 20 minutes.

[0056] 5. Drawing: Use 8t combined drawing machine for Φ14mm drawing.

[0057] 6. Finished product aging: Argon is used as the protective gas, and the Φ14mm drawn product is subjected to bright annealing at 480℃ for 4.5h, with an argon flow rate of 25m 3 / h.

[0058] 7. Performance test: 10 samples were randomly selected for performance test. The performance is shown in Table 3.

[0059] Example 4

[0060] A method for preparing a high-performance chromium bronze rod, comprising the following specific steps:

[0061] 1. Smelting: Cathode copper purity ≥ 99.99%, Cu-Cr master alloy (Cr50%), Cu-Ti master alloy (Ti content 50%), Cu-Mg master alloy (Mg content 50%), single Ag purity ≥ 99.99%, all elements are added according to mass percentage. The ingredients are shown in Table 1, and the smelting parameters are shown in Table 2.

[0062] 2. Electromagnetic stirring: The molten copper enters the crystallizer after smelting. The superheat of the copper in the crystallizer is eliminated by electromagnetic stirring, and the grains of the ingot are refined to obtain an equiaxed crystal structure.

[0063] 3. Water seal extrusion: 3150t extruder is used for water seal extrusion, the extrusion temperature is 910℃, the extrusion speed is 8mm / s, the extrusion ratio is 268, the extrusion specification is Φ16mm, and the cooling water cooling speed is 110℃ / s.

[0064] 4. Pickling: Place the Φ16mm extruded billet into a pickling tank with H2SO4:HNO3:H2O=5.7:1:12.5 (volume ratio) for pickling and soaking for 30 minutes.

[0065] 5. Drawing: Use 8t combined drawing machine for Φ14mm drawing.

[0066] 6. Finished product aging: Argon is used as the protective gas, and the Φ14mm drawn product is subjected to bright annealing at 460℃ for 4.5h, with an argon flow rate of 25m 3 / h.

[0067] 7. Performance test: 10 samples were randomly selected for performance test. The performance is shown in Table 3.

[0068] Example 5

[0069] A method for preparing a high-performance chromium bronze rod, comprising the following specific steps:

[0070] 1. Smelting: Cathode copper purity ≥ 99.99%, Cu-Cr master alloy (Cr50%), Cu-Ti master alloy (Ti content 50%), Cu-Mg master alloy (Mg content 50%), single Ag purity ≥ 99.99%, all elements are added according to mass percentage. The ingredients are shown in Table 1, and the smelting parameters are shown in Table 2.

[0071] 2. Electromagnetic stirring: The molten copper enters the crystallizer after smelting. The superheat of the copper in the crystallizer is eliminated by electromagnetic stirring, and the grains of the ingot are refined to obtain an equiaxed crystal structure.

[0072] 3. Water seal extrusion: 3150t extruder is used for water seal extrusion, the extrusion temperature is 920℃, the extrusion speed is 11mm / s, the extrusion ratio is 268, the extrusion specification is Φ16mm, and the cooling water cooling speed is 110℃ / s.

[0073] 4. Pickling: Place the Φ16mm extruded billet into a pickling tank with H2SO4:HNO3:H2O=5.7:1:12.5 (volume ratio) for pickling and soaking for 35 minutes.

[0074] 5. Drawing: Use 8t combined drawing machine for Φ14mm drawing.

[0075] 6. Finished product aging: Argon is used as the protective gas, and the Φ14mm drawn product is subjected to bright annealing at 470℃ for 4h, with an argon flow rate of 25m 3 / h.

[0076] 7. Performance test: 10 samples were randomly selected for performance test. The performance is shown in Table 3.

[0077] Comparative example: C18200Φ14mm bars were purchased from the market.

[0078] Table 1 Ingredients

[0079]

[0080]

[0081] Table 2 Melting parameters

[0082] Example Melting temperature / ℃ Casting speed mm / s <![CDATA[Cooling water flow rate m 3 / h]]> Cooling water temperature℃ 1 1280 55 15 20 2 1260 60 16 20 3 1270 60 17 25 4 1250 65 14 25 5 1290 65 17 25

[0083] Table 3 Finished product performance

[0084]

[0085]

[0086] From the above test results, it can be seen that the chromium bronze rod prepared by the present invention has excellent performance, conductivity ≥85%IACS, tensile strength ≥650Mpa, softening temperature ≥650℃, A100mm ≥20%, hardness ≥90HRB, which can meet the needs of future high-temperature switch materials.

Claims

1. A high performance chromium bronze bar, characterized in that: The alloy composition of the chromium bronze rod is Cr: 0.2-0.65%, Ti: 0.1-0.5%, Ag: 0.1-0.5%, Mg: 0.1-0.5%, and Cu balance, and the percentages of the above elements are mass percentages; The microstructure dislocation density of the chromium bronze rod is 1.0-10.0×10 14 / mm 2 , grain size is 5-10μm; In the structure of the chromium bronze rod, the size of the Cr precipitated phase is 8nm≤≤15nm, the aspect ratio is 1≤≤1.2, the shape is approximately spherical, and the number of fcc face-centered cubic lattices is ≥98%; In the structure of the chromium bronze rod, the size of Ti2Cu and TiCu precipitated phases is 10nm≤≤20nm, the aspect ratio of the two phases is 1≤≤1.2, and the shape is approximately spherical; The chromium bronze rod has a structure in which the size of the Ag precipitated phase is 10nm≤≤25nm, the aspect ratio is 1≤≤1.3, and the shape is approximately spherical; In the structure of the chromium bronze rod, the size of the Mg precipitate phase is 10nm≤≤25nm, the aspect ratio is 1≤≤1.2, and the shape is approximately spherical.

2. A method for preparing the high performance chromium bronze rod according to claim 1, characterized in that The following steps are involved: 1) Melting: The materials are prepared according to the alloy composition of the chromium bronze bars and melted in a semi-continuous casting furnace; 2) Electromagnetic stirring: The molten copper enters the crystallizer after smelting. The electromagnetic stirring eliminates the superheat of the copper in the crystallizer, refines the grains of the ingot, and obtains an equiaxed crystal structure; 3) Water-seal extrusion: Place the ingot into a large-tonnage reverse extruder for water-seal extrusion, with an extrusion temperature of 900-950°C, an extrusion ratio of 6-310, an extrusion speed of 3-20mm / s, and a cooling water cooling speed of 80-120°C / s; 4) Pickling: put the extruded blank into the pickling tank for pickling; 5) Drawing: Use a combined drawing machine to produce straight bars; 6) Finished product aging: Under protective gas, the finished product is bright annealed at an aging temperature of 400-500℃ for 3-5h.

3. The preparation method according to claim 2, characterized in that: The current frequency of the electromagnetic stirring in step 2) is 10-15H Z , the current intensity is 350-400A, the number of equiaxed grains in the ingot structure is ≥90%, and the equiaxed grain size is 0.005-0.01mm.

4. The preparation method according to claim 2, characterized in that: The raw materials prepared in step 1) according to the alloy composition of the chromium bronze rod are: cathode copper with a purity of ≥99.99%, Cu-Cr master alloy, Cu-Ti master alloy, Cu-Mg master alloy and single substance Ag with a purity of ≥99.99%, wherein the Ti content of the Cu-Ti master alloy is 50%, the Cr content of the Cu-Cr master alloy is 50%, and the Mg content of the Cu-Mg master alloy is 50%; the smelting process parameters of step 1) are: casting temperature 1250-1300°C, pulling speed 55-65mm / min, cooling water temperature 20-25°C, cooling water flow rate 14-17m 3 / h.

5. The preparation method according to claim 2, characterized in that: The pickling in step 4) refers to immersing the finished product in pickling water with a mass ratio of H2SO4:HNO3:H2O=5.7±0.1:1±0.1:12.5±0.1 for 20-60 minutes.

Citation Information

Patent Citations

  • Chromium-bronze alloy board for crystallizer and processing technique thereof

    CN101265537A

  • Copper-chromium-titanium alloy contact wire and preparation method thereof

    CN103966475A

  • Short-process preparing method for high-strength and high-conduction Cu-Cr-Ag alloy

    CN108277378A

  • Free-cutting chromium zirconium copper and preparation method thereof

    CN113584341A